Researching Memoir-based Stories of Jewish Suffering during the Second World War - Hajduk-Nijakowska, Janina (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
Memoirs and the so-called oral testimonies provide a valuable source for learning about the microhistory of individual people’s experience connected with the tragedy of the Jews during the Second World War. This has been proved by researchers from the Polish Centre for Holocaust Research of the Polish Academy of Sciences and their extensive work published in 2018 under the title Dalej jest noc, Losy Żydów w wybranych powiatach okupowanej Polski [„Night without End: The Fate of Jews in Selected Counties of Occupied Poland”]. As I argue, the memoir-based stories collected by folklore researcher Dionizjusz Czubala in the many years of his field studies connected with this subject matter can substantially enrich the analysis of the current memory of those tragic events. Unfortunately, the way these stories were edited by Piotr Grochowski in the volume entitled O tym nie wolno mówić… Zagłada Żydów w opowieściach wspomnieniowych ze zbiorów Dionizjusza Czubali ["We are not allowed to speak about it. The extermination of the Jews in memoirs from the collection of Dionizjusz Czubala"] (2019) does not offer such a possibility. I would like to question not only the very method in which these texts were edited but also their order in the anthology, which reveals the traditional (illustrative) approach to the materials collected in field studies. As a result, the reader cannot follow the process of changes occurring in the narrators’ attitudes to the Jewish themes and problems. Moreover, I also argue against Grochowski’s positioning the memoirs somewhere “between” research practices from the sphere of folklore studies and oral history. Finally, I propose that the value of materials obtained with the use of the oral history method resides in analyses and interpretations coming from different scientific domains.